PENINGKATKAN HASIL BELAJAR MELALUI MODEL TGT (TEAMS GAMES TOURNAMENT) PADA MATAPELAJARAN MATEMATIKA DI SD NEGERI 4 JATI MULYO - Sumarni (STKIP Al Islam Tunas Bangsa dan HEPI Korda Lampung, 2019)
This research was conducted to examine the use of TGT (Teams Games Tournament) as the effort to improve student learning outcomes in mathematics in grade II SD Negeri 4 Jatimuyo Jati Agung subdistrict South Lampung.This research is a class action research which used sample of 20 students in the Class II SDN 4 Jati Agung subdistrict South Lampung regency. The research process is conducted through three cycles of the overall data were taken using observation and tests. The results showed that the use TGT (Teams Games Tournament) has a positive impact on learning outcomes. It can be seen from the increase in the students’ score as well as the learning activities in the classroom which proves the method TGT (Teams Games Tournament) in Mathematics can improve student learning achievement. Thus the method of TGT as an effort to improve student learning outcomes in learning in mathematics class II SDN 4 Mulyo Jati Agung Jati subdistrict South Lampung regency in the academic year 2014/2015 is proven to improve learning outcomes. Keywords: TGT (Teams Games Tournament), learning outcomes, learning activities